2017
DOI: 10.1007/s11631-017-0162-6
|View full text |Cite|
|
Sign up to set email alerts
|

The oceanic cycles of the transition metals and their isotopes

Abstract: The stable isotope systems of the transition metals potentially provide constraints on the current and past operation of the biological pump, and on the state of ocean redox in Earth history. Here we focus on two exemplar metals, nickel (Ni) and zinc (Zn). The oceanic dissolved pool of both elements is isotopically heavier than the known inputs, implying an output with light isotope compositions. The modern oceanic cycle of both these elements is dominated by biological uptake into photosynthesised organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…As a general trend, Ni isotope systematics shows an isotopically heavier Ni pool in the dissolved fraction (-3.35& < D 60/58 Ni solid-aq < À0.11&, Fig. 5), as observed in environmental studies dealing with dissolved Ni in river and seawater (Archer et al, 2020;Cameron & Vance, 2014;Takano et al, 2017;Vance et al, 2017;Wang et al, 2019). Given that no redox chemistry is expected for Ni during "natural processes", the isotope fractionation results from differences in the coordination geometry between Ni dissolved in solution (also depending on Ni aqueous speciation, Fujii et al, 2011Fujii et al, , 2014 and Ni adsorbed onto the solid phase (Schauble, 2004).…”
Section: Ni Complexationsupporting
confidence: 61%
“…As a general trend, Ni isotope systematics shows an isotopically heavier Ni pool in the dissolved fraction (-3.35& < D 60/58 Ni solid-aq < À0.11&, Fig. 5), as observed in environmental studies dealing with dissolved Ni in river and seawater (Archer et al, 2020;Cameron & Vance, 2014;Takano et al, 2017;Vance et al, 2017;Wang et al, 2019). Given that no redox chemistry is expected for Ni during "natural processes", the isotope fractionation results from differences in the coordination geometry between Ni dissolved in solution (also depending on Ni aqueous speciation, Fujii et al, 2011Fujii et al, , 2014 and Ni adsorbed onto the solid phase (Schauble, 2004).…”
Section: Ni Complexationsupporting
confidence: 61%
“…Up to now, heavy δ 60 Ni (i.e. higher than BSE) were exclusively attributed to the dissolved phase of rivers and Oceans, as well as marine sediments and Fe-Mn crusts (Gall et al, 2013;Cameron and Vance, 2014;Porter et al, 2014;Gueguen et al, 2016;Vance et al, 2016;Vance et al, 2017).…”
Section: Published δ 60mentioning
confidence: 98%
“…To explain the relatively heavy Ni isotope composition of the Ocean and Fe-Mn crusts (the main Ni output from the Ocean; average δ 60 Ni = 1.74 ± 0.59‰, n = 126, Gall et al, 2013;Gueguen et al, 2016), the overall input of Ni to the Ocean must be isotopically heavy. Recently, Vance et al (2017) suggested that the heavy Ni isotope composition of the oceanic dissolved pool is the result of the sequestration of light isotopes to sulfides in anoxic and organic-rich sediments. However, the sequestration of isotopically light Ni by iron oxide has also been observed on continents (Estrade et al, 2015;Ratié et al, 2015;Wasylenki et al, 2015, Wang andWasylenki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A more complete understanding of the role of aqueous speciation, and in particular the impact of Ni-organic complexes and their influence on adsorption to mineral surfaces, will undoubtedly help to explain Ni isotope cycling in seawater,weathering environments, and its incorporation in marine sediments. (Cameron and Vance, 2014;Vance et al, 2017;Vance et al, 2016). Laboratory studies comparing Ni partitioning to Fe and Mn oxides to Ni precipitation as a sulfide mineral should be a promising future research direction to develop the Ni isotope tracer for different oxidation-reduction regimes.…”
Section: Aqueous Ni Speciation Is Another Potential Influence On Ni Imentioning
confidence: 99%